Abortion associated with postpartum opportunistic bacterial invasion reduces fertility and induces disturbances of reproductive hormones, hematological profile, and oxidant/antioxidant profiles in dairy cows (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The following study examines for the first time the changes that occur in the post-partum period following abortion in the first trimester of dairy cows using hormonal, hematological, and oxidant/antioxidant profiles. In addition, a bacteriological examination was also performed to explore the role of infections in the complications that occur during this period. Materials and Methods: One hundred cows were split into two equal groups: The first group enrolled cows that suffered from abortion in the first trimester. The second group enrolled cows that did not experience abortion problems (the control group). Uterine swabs were collected from cows. Blood samples were collected for hormonal, hematological, and oxidative profiles. Results: Results reveal that Escherichia coli, Staphylococcus spp., and Streptococcus spp. are the opportunistic bacteria that were isolated from abortive cows with multidrug-resistant (MDR) characteristics. Red blood cell (RBC) count, hemoglobin, mean corpuscular hemoglobin (MCH), and MCH concentration (MCHC) were significantly higher in the abortive group than in controls in the first 3 days after calving. Conversely, total leukocyte count, platelet count, neutrophils, eosinophils, and immunoglobulin G and M were significantly lower in the abortion group than in controls. The concentrations of estradiol, prostaglandin F2α, oxytocin, and cortisol are significantly increased in the abortive cows, while progesterone is significantly decreased. The levels of malondialdehyde (MDA) were higher in the abortive group, while the levels of superoxide dismutase (SOD), glutathione peroxidase (GPx), and total antioxidant capacity (TAC) were lower. Conclusion: Abortion during the first trimester of pregnancy increases the risk of postpartum opportunistic bacterial invasion of the uterus. Oxidative stress (OS) and neutropenia are the most important findings that may occur in the postpartum period after abortion and may be due to the abortion itself or its predisposition to opportunistic bacterial invasion of the uterus, which finally causes a fertility reduction.J. Adv. Vet. Anim. Res., 10(4): 654–666, December 2023http://doi.org/10.5455/javar.2023.j721